PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF PADA MATERI KOORDINAT KARTESIUS KELAS VIII SMP - Vistri Wulandari (Jurnal Edukasi dan Penelitian Matematika, 2021)
Abstract – The goals of this research is to create and describe interactive learning multimedia on valid and practical Cartesian coordinates material for students of class VIII SMPN 7 Sijunjung. The research type used is development research. The Plomp development model was used, which consists of three phases. They are the preliminary research, prototyping phase, and assessment phase. The students of class VIII SMPN 7 Sijunjung are the subject of the research. Needs analysis, curriculum analysis, concept analysis, and student analysis were conducted as part of the preliminary research phase for the development of interactive multimedia learning on Cartesian coordinates. The phase of prototyping aims to develop interactive learning multimedia in order to produce the interactive learning multimedia valid and practical through formative evaluation. They are self evaluation, expert review, one-to-one evaluation, and small group evaluation. The result of the validity value of interactive learning multimedia on the Cartesian coordinate material is 84,38% with a very valid category. Based on the results of the practicality questionnaire analysis by students and teachers, it is shown that interactive multimedia learning on Cartesian coordinate material in all aspects is in the very practical category with practicality values of 88,54% and 95,45%. As a result, interactive learning multimedia on Cartesian coordinates for class VIII SMP is valid, practical, and can be used. Keywords– interactive learning multimedia, Cartesian coordinates, valid, practical